2017
DOI: 10.1177/0885066617705641
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Bronchoscopy-Guided and Real-Time Ultrasound-Guided Percutaneous Dilatational Tracheostomy: Safety, Complications, and Effectiveness in Critically Ill Patients

Abstract: Ultrasound-guided percutaneous dilatational tracheostomy is a safe procedure for critically ill patients and has the advantages of a low complication rate, short duration of procedure, being informative with regard to neck anatomy, and facilitating prevention of vascular puncture. Thus, US-PDT can be used as an alternative to FOB-PDT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 14 publications
0
37
0
Order By: Relevance
“…12 Ultrasound has proved to diminish the duration of the procedure, as well as the hemorrhage associated with it. 7 It has also been observed that episodes of oxygen desaturation (<90%) are less frequent when this technique is used. 13 Because of this advantage, US imaging has been suggested as the first-line technique for percutaneous dilatational tracheostomies in patients with neck anatomic abnormalities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…12 Ultrasound has proved to diminish the duration of the procedure, as well as the hemorrhage associated with it. 7 It has also been observed that episodes of oxygen desaturation (<90%) are less frequent when this technique is used. 13 Because of this advantage, US imaging has been suggested as the first-line technique for percutaneous dilatational tracheostomies in patients with neck anatomic abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous trial, a US‐guided percutaneous dilatational tracheostomy proved not to be inferior to a bronchoscopy‐guided percutaneous dilatational tracheostomy . Ultrasound has proved to diminish the duration of the procedure, as well as the hemorrhage associated with it . It has also been observed that episodes of oxygen desaturation (<90%) are less frequent when this technique is used .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…US has several advantages, such as high portability, safety, and reliability; furthermore, it is a pain free, simple procedure (10,11). Many studies have stated that the use of PDT with real time US is a reliable and effective method that reduces complications (12,13).…”
Section: Discussionmentioning
confidence: 99%
“…7 Thus, when assessing the safety of PDT with US and bronchoscopic guidance in critically ill patients, in addition to complications, the study design should also include intergroup comparisons with respect to the quality of ventilation, analysis of blood gases, and the PaO 2 -to-FIO 2 ratio, as performed in previous studies. [5][6][7][8] Chao Wen, MD, Fu-Shan Xue, MD , Jin-Hua Jin, MD, Qing Liu, MD…”
mentioning
confidence: 99%